Understanding the presence of mental fatigue in elite female football - Thompson, C. J.; Smith, A.; Coutts, A. J.; Skorski, S.; Datson, N.; Smith, M. R.; Meyer, T. (Research Quarterly for Exercise and Sport, 2022)
Purpose: Previous research investigating the impact of induced mental fatigue in football (soccer) has demonstrated associated performance decrements in physical, technical, tactical and decision-making performance. A common limitation amongst this research is the protocols used to induce mental fatigue which provides low ecological validity, and the inclusion of recreational or sub-elite players. Therefore, understanding the presence of mental fatigue in elite football can provide insight into protocols with greater ecological validity. Methods: The current study used focus groups with 10 elite female football players, focusing on five topics (travel, fixture congestion, receiving tactical information, pre-match routine and pressure to win) related to the perceived causes of mental fatigue in elite football (directed by anecdotal quotes in elite football and research-based theories). Results: Several themes emerged from the data; travel fatigue, inability to switch off from football, fatigue experienced following team meetings, use of pre-match music and internal pressure to succeed. Conclusion: These findings present practical recommendations to reduce mental fatigue in elite football settings, such as considering the timing, content and duration of team meetings, providing players with free time/rest where possible, and considering the modality of coaching instructions during matches.